Development of Cloud-Based Agriculture Marketing System with Intellectual Weigh Machine. Issue 1 (February 2021) - Anbumani, V; Geetha, V; Praveen Kumar, V; Sabaree, D; Sivanantham, K
Abstract: Agriculture is the backbone of Indian economy. Agriculture is most important occupation for the maximum number of the Indian families. Though technologies developed so much still farmers did not get the reasonable price in the market for their agricultural products because of intermediaries. Today most of the distribution systems are facing many challenges like intermediaries, in between the producers and the customers, seeking to earn more profit. Hence there is need for a more regularized system to avoid the intermediaries and agriculturist should get more gain out of their product. The aim of the system is to develop a better, efficient marketing system using intellectual weighing system using Load cell, Raspberry-pi module. It includes security and easy consolidation of the bill. The conventional system has intermediaries because of whom the profit of the producer will be getting affected. In the existing system, works which include entry, product weighing, product distribution and product delivery are done manually. Proposed system includes proper data from the databases to be sent to corresponding users. It facilitates the interaction between producer and buyers and enables the buyer to buy product easily. Stock maintenance in the distribution center is established.